Emissions Trading as a Guiding Instrument for an Effective and Efficient EU Climate Policy in Transport - Alexander Eisenkopf; Andreas Knorr (Wirtschaftsdienst)
Abstract The European Union’s top climate policy objective is to fully decarbonise its member states’ economies by 2050, i. e. to achieve climate neutrality in all sectors that currently still depend on fossil fuels. This is fully reflected in the EU Commission’s political agenda under the heading “European Green Deal”. In order to achieve climate neutrality by 2050, the EU’s previous intermediate CO2 reduction target was recently tightened from a 40 % to a 55 % reduction by 2030. In its “Fit for 55 Program”, which was announced on 14 July 2021, the Commission proposed comprehensive reforms of the EU’s emissions trading system, the Renewable Energies Directive and the Energy Tax Directive to fully implement the European Green Deal. This paper provides a critical assessment of the proposed measures.